TRADISI BISNIS DI PESANTREN - Siti Nur Azizah (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes and analyzes the business tradition in Islamicboarding school as an alternative economics empowering for theschool and its society. The data is collected by observation, interviewand documentation. This study shows that Mamba’ul Ulum boarding schoolcould preserve its life by eco-protective development, e.g. animal husbandry,farming, and cooperative development. Those three activities havea powerful basic in its neighborhood.